Ochrona przeciwpowodziowa na lubuskim odcinku Odry granicznej = Flood control on lubuskie province of Odra border-river - Kołodziejczyk, Urszula; Warcholak, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Odra in considerable parts determines border with Germany. In precincts of lubuskie province is found 76, 2 km section of border-river Odra. This places before authorities of province additional assignments relating Odra development and flood-protections. On lubuski section of border-river Odra till now one modenized 43,03 km of embankments, and at present are driven repair works on following sections lengths 12. 47 km. To 2030 plans oneself making of further works embracing modernization of existing flood-control objects.
Keywords: Odra; powódź; badania